First evidence of enterovirus A71 and echovirus 30 in Uruguay and genetic relationship with strains circulating in the South American region. - Andrés Lizasoain (Public Library of Science (PLoS), 2021)
Human enteroviruses (EVs) comprise more than 100 types of coxsackievirus, echovirus, poliovirus and numbered enteroviruses, which are mainly transmitted by the faecal-oral route leading to diverse diseases such as aseptic meningitis, encephalitis, and acute flaccid paralysis, among others. Since enteroviruses are excreted in faeces, wastewater-based epidemiology approaches are useful to describe EV diversity in a community. In Uruguay, knowledge about enteroviruses is extremely limited. This study assessed the diversity of enteroviruses through Illumina next-generation sequencing of VP1-amplicons obtained by RT-PCR directly applied to viral concentrates of 84 wastewater samples collected in Uruguay during 2011-2012 and 2017-2018. Fifty out of the 84 samples were positive for enteroviruses. There were detected 27 different types belonging to Enterovirus A species (CVA2-A6, A10, A16, EV-A71, A90), Enterovirus B species (CVA9, B1-B5, E1, E6, E11, E14, E21, E30) and Enterovirus C species (CVA1, A13, A19, A22, A24, EV-C99). Enterovirus A71 (EV-A71) and echovirus 30 (E30) strains were studied more in depth through phylogenetic analysis, together with some strains previously detected by us in Argentina. Results unveiled that EV-A71 sub-genogroup C2 circulates in both countries at least since 2011-2012, and that the C1-like emerging variant recently entered in Argentina. We also confirmed the circulation of echovirus 30 genotypes E and F in Argentina, and reported the detection of genotype E in Uruguay. To the best of our knowledge this is the first report of the EV-A71 C1-like emerging variant in South-America, and the first report of EV-A71 and E30 in Uruguay.